Organic media-based two-stage traditional and electrode-integrated tidal flow wetlands to treat landfill leachate: Influence of aeration strategy and plants. (15th March 2023) - Saeed, Tanveer; Zaman, Takrim; Miah, Md Jihad; Yadav, Asheesh Kumar; Majed, Nehreen
Abstract: Landfill leachate treatment employing normal and electrode-integrated constructed wetlands is difficult due to the presence of significant amounts of organic compounds, which frequently impede the progression of microbial-based aerobic pollutant removal pathways. As a result, this study examines the effect of supplementary air availability via intermittent and continuous aeration strategies in improving organic, nutrient, and coliform removals of the unplanted, planted (normal and electrode-integrated) two-stage tidal flow constructed wetlands designed to treat landfill leachate. The constructed wetlands were filled with coal and biochar media and planted with Canna indica . Mean chemical oxygen demand (COD), total nitrogen (TN), total phosphorus (TP), and coliform removal percentages of the externally aerated two-stage unplanted, only planted, planted-microbial fuel cell integrated constructed wetland systems ranged between 96 and 99%, 82 and 93%, 91 and 98%, 86 and 96%, respectively, throughout the experimental campaign. External aeration inhibited the development of a dominant anaerobic environment within the media of the wetland systems and improved overall pollutant removal. The electrode-integrated planted tidal flow wetlands produced better effluent quality than the unplanted or only planted tidal flow systems without electrode assistance. The first stages of the three wetland systems achieved an additional 5–7% COD, 7–12% TN, and 15–22% coliform removal during the continuous aeration period compared to the corresponding performance of the intermittent aeration phase. The pollutant removal performance of the second-stage wetlands decreased during the continuous aeration phase. The media composition supported electrochemically active and inactive microbial-based pollutant removal routes and the chemical adsorption of pollutants. Nitrogen and phosphorus accumulation percentage in plant tissues was low, i.e., 0.4–2.2% and 0.04–0.8%, respectively. During the continuous aeration period, the electrode-integrated tidal flow constructed wetlands achieved higher power density production, i.e., between 859 and 1432 mW (mW)/meter 3 (m 3 ). This study demonstrates that external aeration might improve pollutant removal performance of the normal, electrodes integrated tidal flow-based constructed wetlands when employed for high organic-strength wastewater treatment such as landfill leachate. Graphical abstract: Image 1 Highlights: Normal and electrode-assisted aerated tidal flow wetlands treated leachate. Plants, electrodes, and aeration have a positive synergistic effect on performance. 96–99% COD, 82–94% TN, 91–98% TP, and 86–96% coliform removals were achieved. The nutrient accumulation percentage in plant tissues ranged between 0.02 and 2.2%. A maximum power density production of 1572 mW/m 3 was recorded.